Pendampingan Pembuatan dan Manajemen OJS Pendekar Sebagai Wadah Publikasi Hasil Pengabdian Kepada Masyarakat di Universitas Batam - Frangky Silitonga; Kartika Cahayani; M Muthma'innah (LPPM-STIT Hidayatullah Batam, 2024)
This service is assistance in creating a forum for the publication of Community Service results at Batam University. In the creation and management activities of OJS Pendekar, this is a collaborative service between the Batam Tourism Polytechnic and Batam University. The target achievement of this assistance is to create a journal house, with the name adasar, whose function is to publish the results of Community Service activities (PKM) carried out by the Batam University academic community. This PKM is carried out online and offline from the Batam Tourism Polytechnic and Batam University. The PKM implementation method is carried out face to face with the aim of managing OJS Pendekar, while the online method aims to complete administration at BRIN and internally. The application of the face to facetoface method used is lectures, role plays and demonstrations as well as direct practice which has been scheduled in a regular and structured manner. The results obtained were that the OJS Pendekar’s Editorial Board and participants were able to register an account at OJS as a writer or reviewer or. Create publication sections, issues and how to publish each article that has been submitted to OJS Pendekar. The limitations of varying PC’s specifications, time and instruments used during this service activity assistance activity can be minimized with the support of internet access technology as well as the enthusiasm of the activity participants and a family atmosphere to work together to advance Batam University in supporting the Tridharma of Higher Education.